THE IMPORTANCE OF THE PROFESSION SOCIAL PEDAGOGUE IN THE FIELD OF PUBLIC EDUCATION (Education in the 21st Century, 2023)
The purpose of the research: The purpose of the research is to study the importance of the "social pedagogue" profession in the field of public education.The novelty of the research: the professional functions of class teachers, teacher assistants, and social pedagogues were researched and compared. The social pedagogue was found to be most important to general education.The article examines the importance of the profession of "social pedagogue" in the field of public education.It is justified that the activity of class leaders and teacher's assistants is not always appropriate in the general education school and in some cases causes a conflict with the functions of the social pedagogue.It is necessary to jointly discuss the functions of class teachers, social pedagogue and teacher's assistants and review the assigned positions.If we keep in mind that the acquisition of the profession of "social pedagogue" is conditioned by the availability of an appropriate educational program and the demand of the labor market, while a special training is not implied for the positions listed above, then it is advisable to review the assigned positions, replace the class teacher institute with "social pedagogue" institute, to expand their functions with the presence of mandatory positions of psychologists in public schools, to form a cooperative team that will be able to solve the problems arising during the socialization of students.
Keywords: social pedagogue; social pedagogue functions; teacher's assistant; social pedagogue activity spheres